THE PHILOSOPHICAL BASIS OF THE COMPETENCE TO ADJUDICATE BANKRUPTCY CASES INVOLVING AN ARBITRATION CLAUSE - Adhypratama, Bayu (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2021)
This research stems from the conflict of competence between Commercial Court and Arbitration in a bankruptcy case involving an arbitration clause. This occurs when parties make an agreement including arbitration as a mechanism of dispute resolution. Nevertheless, when a dispute occurs, one of the parties file a bankruptcy petition to Commercial Court as contained in Article 303 of the Bankruptcy Law. Meanwhile, according to Article 3 and 11 of the Arbitration Law, agreements containing arbitration clause as a mean of dispute resolution provides absolute competence, which is consistent with the pacta sunt servanda principle outlined by Article 1338 of the Civil Code. This raises the question of whether Article 303 of the Bankruptcy Law is inconsistent with pacta sunt servanda or to the arbitration clause as the agreed mechanism of dispute resolution by the parties, because the substance of legal norms has philosophical basis. This research uses normative juridical approach which examines legal materials through the study of documents. The research show that Commercial Court is an extra ordinary court which settle bankruptcy filed to the court. Therefore, the competence cannot be set aside by arbitration in the sense of its legal position and capacity as extra judicial even though it originates from an agreement containing arbitration clause. The philosophical basis that can be applied in the conflict of law refers to the principles governing legislation, namely lex specialis derogat legi generalis, lex posterior derogat legi priori, and integration principles of Article 303 of the Bankruptcy Law.